2023
DOI: 10.1002/iid3.952
|View full text |Cite
|
Sign up to set email alerts
|

Propofol synergizes with circAPBB2 to protect against hypoxia/reoxygenation‐induced oxidative stress, inflammation, and apoptosis of human cardiomyocytes

Abstract: BackgroundMyocardial injury is the main manifestation of cardiovascular diseases, and previous studies have shown that propofol (PPF) regulates myocardial injury. However, the mechanism of PPF in regulating myocardial injury remains to be further explored. This work aims to analyze the effects of PPF on human cardiomyocyte injury and the underlying mechanism.MethodsThe regulatory and functional role of PPF and circAPBB2 in human cardiomyocyte injury were analyzed using an in vitro hypoxia/reoxygenation (H/R) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Lactate and valine are both common serum metabolites that were similarly found in this study to potentially influence the risk of developing atrial fibrillation. It has been demonstrated that lactate accelerates vascular calcification and leads to mitochondrial dysfunction, and that valine exhibits antiarrhythmic effects in ischaemia–reperfusion experiments, mechanisms of action that may be closely related to cardiomyocyte apoptosis and inflammatory responses [ 49 51 ]. Meanwhile, combined with the results of our intestinal flora MR analyses, it was demonstrated that flora such as Bactericide and genus Odoribacter are strongly associated with lactate and valine, but the mechanism of action in disease remains unclear [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate and valine are both common serum metabolites that were similarly found in this study to potentially influence the risk of developing atrial fibrillation. It has been demonstrated that lactate accelerates vascular calcification and leads to mitochondrial dysfunction, and that valine exhibits antiarrhythmic effects in ischaemia–reperfusion experiments, mechanisms of action that may be closely related to cardiomyocyte apoptosis and inflammatory responses [ 49 51 ]. Meanwhile, combined with the results of our intestinal flora MR analyses, it was demonstrated that flora such as Bactericide and genus Odoribacter are strongly associated with lactate and valine, but the mechanism of action in disease remains unclear [ 52 ].…”
Section: Discussionmentioning
confidence: 99%